Monitoring Moroccan Honeys: Physicochemical Properties and Contamination Pattern - Massous, Abir; Ouchbani, Tarik; Lo Turco, Vincenzo; Litrenta, Federica; Nava, Vincenzo; Albergamo, Ambrogina; Potortì, Angela Giorgia; Di Bella, Giuseppa (Foods, 2023)
The physicochemical traits and an array of organic and inorganic contaminants were monitored in monofloral honeys (i.e., jujube [Ziziphus lotus], sweet orange [Citrus sinensis], PGI Euphorbia [Euphorbia resinifera] and Globularia alyphum) from the Moroccan Béni Mellal-Khénifra region (i.e., Khénifra, Beni Méllal, Azlal and Fquih Ben Salah provinces). Moroccan honeys were in line with the physicochemical standards set by the European Union. However, a critical contamination pattern has been outlined. In fact, jujube, sweet orange, and PGI Euphorbia honeys contained pesticides, such as acephate, dimethoate, diazinon, alachlor, carbofuran and fenthion sulfoxide, higher than the relative EU Maximum Residue Levels. The banned 2,3′,4,4′,5-pentachlorobiphenyl (PCB118) and 2,2′,3,4,4′,5,5′-heptachlorobiphenyl (PCB180) were detected in all samples and quantified in jujube, sweet orange and PGI Euphorbia honeys; while polycyclic aromatic hydrocarbons (PAHs), such as chrysene and fluorene, stood out for their higher contents in jujube and sweet orange honeys. Considering plasticizers, all honeys showed an excessive amount of dibutyl phthalate (DBP), when (improperly) considering the relative EU Specific Migration Limit. Furthermore, sweet orange, PGI Euphorbia and G. alypum honeys were characterized by Pb exceeding the EU Maximum Level. Overall, data from this study may encourage Moroccan governmental bodies to strengthen their monitoring activity in beekeeping and to find suitable solutions for implementing more sustainable agricultural practices.